Colocolic Intussusception in Children: A Case Series and Review of the Literature - Yan, Jiayu; Shen, Qiulong; Peng, Chunhui; Pang, Wenbo; Chen, Yajun (Frontiers in Surgery, 2022)
Background: Colocolic intussusceptions is a rare subtype of intussusception mostly caused by juvenile polyps. The treatment of colocolic intussusception caused by other pathologic lead points in children remains poorly understood. Method: A systematic literature review was performed between January 2000 and June 2021 to characterize the comprehensive treatment of colocolic intussusception in children. This report also included patients admitted to our center between January 2010 and June 2021who were not previously reported in the literature. Results: We identified 27 patients in 20 studies in addition to 17 patients from our center for a total of 44 patients (median age, 4.4 years; 52.3% male). The lead point was identified in 40 patients (40/44, 90.9%). The most common lead point was juvenile polyps (19/44, 43.2%). A therapeutic enema was performed in 15 patients with colocolic intussusception caused by juvenile polyps and was successful in 9 patients (9/15, 60.0%). Colonoscopic polypectomy was subsequently performed in 8 patients and was successful in 7 patients (7/8, 87.5%). The other patient had undergone laparoscopic exploration, and no abnormality was found. Subsequently, the patient underwent open surgery. The patients with colocolic intussusception caused by other pathologic lead points almost underwent surgical treatment (15/21, 71.4%), including 13 open surgeries and 2 laparoscopic surgeries. Conclusion: A therapeutic enema followed by colonoscopic polypectomy is feasible to treat colocolic intussusception caused by juvenile polyps unless the patient has bowel perforation; however, surgery is sometimes needed. For patients with colocolic intussusception caused by other pathologic lead points, open surgery remains the primary treatment.